Nonlinear tracking control for sensorless permanent magnet synchronous motors with uncertainties. (March 2017) - Verrelli, C.M.; Tomei, P.; Lorenzani, E.; Migliazza, G.; Immovilli, F.
Abstract: The recent advanced solution inMarino, Tomei, and Verrelli (2013) to the tracking control problem for sensorless IMs with parameter uncertainties is translated on the basis of letter swap connections between the models of (nonsalient-pole surface) permanent magnet synchronous motors (PMSMs) and induction ones (IMs). The (stability proof-based) nonlinear adaptive position/speed tracking control for sensorless PMSMs (with simultaneous estimation of uncertain constant load torque and stator resistance), which is accordingly obtained by exploring and decoding the design paths inMarino et al. (2013) and which surprisingly represents a simple generalization of the controller inTomei and Verrelli (2011), constitutes an innovative solution to the related open problem. Illustrative experimental results are included.